Hubungan Perilaku Menyikat Gigi dan Kejadian Karies Gigi pada Anak Usia Sekolah di Desa Wori - Wowor, Vonny N. S.; Bernadus, Janno B. B.; Lumbangaol, Grace M. P. (Universitas Sam Ratulangi, 2025)
Abstract: Dental caries is still a significant health problem among school-age children 6 – 12 years in Southeast Asian countries. Tooth brushing behavior plays an important role in oral and dental health status. This study aimed to evaluate the relationship between tooth brushing behavior and the incidence of dental caries among school-age children at Desa Wori. This was an analytical and observational study with a cross-sectional design. Samples of 153 students were selected using the stratified proportionate random sampling technique. We used questionnaire to evaluate the tooth brushing behavior which had been tested for validity and reliability, meanwhile the examination of dental caries was performed using the International Caries Detection and Assessment System (ICDAS). The results showed that 24 students brushed their teeth correctly and did not have dental caries, while 52 students brushed their teeth correctly but had dental caries. Moreover, 10 students had poor brushing behavior but had no dental caries, meanwhile 67 students had poor behavior and had dental caries. The chi-square test obtained a p-value of 0.006 (p≤0.05). In conclusion there is a significant relationship between tooth brushing behavior and the incidence of dental caries among school-age children at Desa Wori. Keywords: tooth brushing behavior; dental caries; school-age children Abstrak: Karies gigi masih merupakan masalah kesehatan yang signifikan pada anak usia sekolah 6–12 tahun di negara-negara Asia Tenggara. Perilaku menyikat gigi memegang peranan penting dalam status kesehatan gigi dan mulut. Penelitian ini bertujuan untuk mengetahui hubungan perilaku menyikat gigi dengan kejadian karies gigi pada anak usia sekolah di Desa Wori. Penelitian ini menggunakan metode observasional analitik dengan desain potong lintang. Partisipan sebanyak 153 siswa dipilih dengan menggunakan teknik stratified proportionate random sampling. Instrumen yang digunakan untuk perilaku menyikat gigi ialah kuesioner yang telah diuji validitas dan reliabilitas serta pemeriksaan karies gigi menggunakan International Caries Detection and Assessment System (ICDAS). Hasil penelitian memperlihatkan bahwa 24 siswa memiliki perilaku menyikat gigi yang baik dan tidak ada karies gigi, sedangkan 52 siswa memiliki perilaku menyikat gigi dengan baik tetapi ada karies gigi. Kemudian ditemukan 10 siswa memiliki perilaku menyikat gigi yang kurang baik dan tidak ada karies gigi, sedangkan 67 siswa memiliki perilaku kurang baik dan ada karies gigi. Uji chi-square mendapatkan nilai p=0,006 (p≤ 0,05). Simpulan penelitian ini ialah terdapat hubungan bermakna antara perilaku menyikat gigi dengan kejadian karies gigi pada anak usia sekolah di Desa Wori. Kata kunci: perilaku menyikat gigi; kejadian karies gigi; anak usia sekolah